Eksplorasi Etnofisika Pada Alat Permen Kapas Sederhana - Patty, Elyakim Nova Supriyedi; Pereira, Agostinho Ximenes; Trisandi, Rina; Ardiansyah, Ardiansyah (Varied Knowledge Journal, 2025)
Cotton candy/arumanist is one of the traditional snacks that is favored by many people. A simple cotton candy/arumanis tool is one of the tools used to make cotton candy/arumanis. This tool consists of several components, namely a heater, wire, and tray. The sugar used in making cotton candy/arumanis can be either powdered sugar or granulated sugar. This research aims to explore the ethnophysics of a simple cotton candy/arumanis tool. The method used is the experimental method. Data was collected by measuring the weight of cotton candy/arumanis produced from the use of powdered sugar and granulated sugar with different weights. The results showed that granulated sugar produced more cotton candy/arumanis than powdered sugar. This is due to the shape of granulated sugar which is larger than refined sugar. Granulated sugar has a larger surface area so it is easier to melt and expand.